Kojic acid reverses LPS-induced neuroinflammation and cognitive impairment by regulating the TLR4/NF-κB signaling pathway - Ali, Waqar; Choe, Kyonghwan; Park, Jun Sung; Ahmad, Riaz; Park, Hyun Young; Kang, Min Hwa; Park, Tae Ju; Kim, Myeong Ok (Frontiers in Pharmacology, 2024)
Intense neuroinflammation contributes in neurodegenerative diseases, such as Alzheimer's diseases and Parkinson's disease. Lipopolysaccharide (LPS) is an integral part of cell wall of gram-negative bacteria act as PAMPs and potentially activates immune system of Central Nervous System (CNS).Microglial cells are the local macrophages of CNS and having potential to induce and control neuroinflammation. This study is aimed to evaluate the anti-inflammatory and antioxidant effect of kojic acid against the toxic effect of LPS, such as neuroinflammation induced neurodegeneration and cognitive decline. The C57BL/6N mice were subjected to LPS injection for two weeks on an alternate day (each mouse received 0.25 mg/kg/i.p. for a total of seven doses), and kojic acid was administered orally for three weeks consecutively (50 mg/kg/mouse, p.o). Bacterial endotoxins, LPS directly attached to TLR4 surface receptors of microglia and astrocytes, which alter the cellular metabolism of immune cells. Intraperitoneal injection of LPS trigger the Toll-Like Receptor 4 (TLR4), phospho-nuclear factor kappa B (p-NFκB), and phospho-c-Jun n-terminal kinase (p-JNK) proteins expressions in LPS treated group which was significantly downregulated in LPS+KA treated mice brain. Prolong neuroinflammation leads to generation of ROS followed by decrease in nuclear factor erythroid-2-related factor 2 (Nrf2) and the enzyme hemeoxygenase 1 (HO-1) expression in LPS subjected mouse brain. But interestingly, the level of both Nrf-2 and HO-1 were increase in LPS+KA treated mice group. In addition, kojic acid inhibited LPS-induced TNF-α and IL-1β production in mouse brain. These results indicated that kojic acid may suppress LPS-induced neuroinflammation and oxidative stress in male wild type mice brain (both in cortex and hippocampus) by regulating TLR4/NF-κB signaling pathway.